Experiencing Notational Artifacts in Music-Making: Towards a Theoretical Framework (Sound Stage Screen, 2021)
Until today, the most traditional media for music notation—scores, parts, or “music books” in general—played an essential role in musicology, providing the essential core of information upon which historical and philological research are grounded. Even if more recent disciplinary turns attempted to undermine the textualist bias according to which “scores were the only real thing about music” (Kenyon), nevertheless the conceptual tools we use to identify, describe, and analyze such scores remained substantially unaltered. Score-like objects are still assigned the status of sources in a research-oriented perspective which prioritizes content forms over usage practices, compositional processes over performative ones, and music writing over music reading. Nevertheless, any material object that incorporates and displays music notation—i.e., a notational artifact—can work not merely as a witness of a musical text, but also as a multi-faceted “bundle of affordances” (Sterne), according to its users and the practices they perform with it.In this article I propose a theoretical framework for analyzing the relationship between user and artifact in music-making. By reframing textual critical tools within a cultural anthropological approach, notational artifacts can be understood as materials with specific physical and visual features; as triggers for a concrete space of human interaction and a symbolic place of belonging; and as repositories for intellectual and operative contents. By applying this framework to one peculiar score belonging to Austrian violinist Rudolf Kolisch, I argue for a reconsideration of the main practices performed by users over their artifacts, namely the acts of writing (notation and annotation), of material production and alteration, and of reading in various music-making processes.
Keywords: material culture; anthropology; music reading; music writing; music-making